2001
DOI: 10.1046/j.1460-9592.2001.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Washing Machine Associated 50 Hz Detected As Ventricular Fibrillation by An Implanted Cardioverter Defibrillator

Abstract: This case report describes a patient with an automatic ICD who suffered a defibrillation shock without warning symptoms. An electrical interference can be observed in the stored EGM of the episode. The patient explained that the moment he felt the shock he was touching a washing machine. After correct grounding of this machine the patient did not suffer more inappropriate shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In this patient, the intracardiac electrocardiogram clearly showed that he was in normal sinus rhythm and the baseline perturbations due to 50 Hz alternating current were falsely detected to be VF. Similar two case reports had been published in which similar inappropriate shocks were given due to electrical interferences while touching washing machine [5,6]. This case report also emphasizes the need for proper grounding of all electrical appliances that are handled by patients with ICD.…”
Section: Case Reportsupporting
confidence: 82%
See 1 more Smart Citation
“…In this patient, the intracardiac electrocardiogram clearly showed that he was in normal sinus rhythm and the baseline perturbations due to 50 Hz alternating current were falsely detected to be VF. Similar two case reports had been published in which similar inappropriate shocks were given due to electrical interferences while touching washing machine [5,6]. This case report also emphasizes the need for proper grounding of all electrical appliances that are handled by patients with ICD.…”
Section: Case Reportsupporting
confidence: 82%
“…Electromagnetic interferences with ICD have been described with various electrical devices like electric razors [1], hand held radiofrequency remote controls [2], slot machines [3], electronic article surveillance systems [4]. A search of literature found two case reports of inappropriate shock delivery related to electrical interference between washing machine and an ICD [5,6]. The present patient had an inappropriate ICD shock when he touched washing machine.…”
mentioning
confidence: 90%
“…Rare reports of malfunction of CIEDs due to EMI from other sources including slot machines, 82 washing machines, 33 power drills, 83 and alternative medicine devices 84 exist in the literature. In general, recipients should be advised to avoid close contact of electrical equipment with CIEDs' generator.…”
Section: Other Routine or Workplace Sourcesmentioning
confidence: 99%
“…Therefore, there is an existing and remaining concern of whether NMES can be applied in these patients, due to fear of electromagnetic interference (EMI). EMI can cause oversensing and lead to inappropriate therapies in ICD patients, resulting in arrhythmias and/or painful shocks [2224]. These patients are generally advised to avoid exposure to electrical currents and electromagnetic sources, even though ICDs seem to be less sensitive to interference than pacemakers [25].…”
Section: Introductionmentioning
confidence: 99%